ADAM15 is an adhesion receptor for platelet GPIIb-IIIa and induces platelet activation - Langer, Harald; May, Andreas E.; Bültmann, Andreas; Gawaz, Meinrad (Thrombosis and Haemostasis, 2005)
Cell adhesion and proteolytic matrix degradation are central processes in atherosclerosis. Being a member of the family of ADAMs (“a disintegrin and metalloproteinase”), metargidin (ADAM15) combines a metalloproteinase domain and an RGD aminoacid sequence. We studied the potential role of ADAM15 as an adhesion receptor on endothelial cells and interactions between platelets and ADAM15 with respect to platelet adhesion, activation and thrombus formation. ADAM15 was found to be expressed on cultured endothelial cells (HUVEC). Platelet adhesion to immobilized recombinantADAM15 was effectively enhanced under both static and high shear rate conditions reaching the maximum level of adhesion to fibrinogen. Consistently, platelet adhesion onto ADAM15 overexpressing endothelial cells was significantly increased. Adhesion to ADAM15 was reduced by blockade of GPIIb-IIIa using neutralizing anti-αIIbβ3 mAbs (7E3, 2G12), but not by anti-αvβ3 (LM609). Soluble ADAM15 binds to activated but not to resting GPIIb-IIIa. Moreover, platelets adherent to ADAM15 additionally attracted platelets under high shear rates indicating an initial role of platelet- ADAM15 interactions for thrombus formation. Furthermore, incubation of platelets with solubleADAM15 showed a dose-dependent increase in secretion of CD62P and CD40L. ADAM15 is expressed on endothelial cells and can serve as an adhesion receptor for platelets via GPIIb-IIIa binding. Platelet adhesion to ADAM15 leads to platelet activation, secretion and promotes thrombus formation. Thus, ADAM15 may represent a novel target for antithrombotic strategies in cardiovascular pathologies.
Keywords: ADAM15; platelets; endothelium; integrin; atherosclerosis